2007
DOI: 10.1111/j.1439-0523.2007.01303.x
|View full text |Cite
|
Sign up to set email alerts
|

Diallel analysis of root‐knot nematode resistance based on galling index in upland cotton

Abstract: The southern root-knot nematode (RKN) [Meloidogyne incognita (Kofoid and White) Chitwood) RKN] is one of the most destructive pests in the Cotton Belt of the U.S. Developing and employing resistant cultivars is the most economical and efficient method for RKN management. This greenhouse investigation was conducted to understand the quantitative genetic basis of RKN resistance in the major RKN resistance sources using a nine-parent diallel analysis based on improved RKN evaluation techniques. The selected genot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…resistance. Zhang et al (2007) observed that partial dominance effects controlled the inheritance of M. incognita resistance in their study involving upland cotton.…”
Section: Genetic Effects For Resistance To Nematodesmentioning
confidence: 95%
See 2 more Smart Citations
“…resistance. Zhang et al (2007) observed that partial dominance effects controlled the inheritance of M. incognita resistance in their study involving upland cotton.…”
Section: Genetic Effects For Resistance To Nematodesmentioning
confidence: 95%
“…However, in cotton (Gossypium spp. ), Zhang et al (2007) found the GCA to be more important than the SCA in the inheritance of M. incognita resistance. The SCA effects were not significant for the number of root lesions and P. zeae densities in all the hybrids (data is not shown), implying that GCA effects make the greatest contribution towards resistance to the P. zeae.…”
Section: Specific Combining Ability (Sca) Effectsmentioning
confidence: 96%
See 1 more Smart Citation
“…Potence ratio showed the over dominant at all variables except root gall intensity that was incomplete dominant and linearly with Zhang et al (2007) result in cotton for root-knot nematode (Meloidogyne incognita (Kofoid and White) Chitwood). The over dominant of resistance to nematode is advantage condition for inventing of resistant tomato hybrid.…”
Section: Discussionmentioning
confidence: 99%
“…Hayman's (1954a, 1954b) diallel analysis method has been used to study the mode of inheritance of various traits in several crops including barley ( Hordeum vulgare L.) (Johnson, 1963; Riggs and Hayter, 1972, 1973; Jana, 1975; Olsen, 1979; Douglas and Gordon, 1985; Caligari et al, 1987; Komatsuda et al, 1989), Brassicas (Ono and Takahata, 2000; Zhang and Takahata, 2001; Sparrow et al, 2004a, 2004b; Tanaka and Niikura, 2006; Horisaki and Niikura, 2007), cotton ( Gossypium hirsutum L.) (Verhalen et al, 1971; Innes et al, 1974; Luckett, 1989; Zhang et al, 2007), maize ( Zea mays L.) (Rood and Major, 1981a, 1981b; Hohls et al, 1996; Betrán et al, 2003; Srdić et al, 2007; Kagoda et al, 2011), pea ( Pisum sativum L.) (Bencheikh and Gallais, 1996), peanut ( Arachis hypogaea L.) (Gibori et al, 1978), radish ( Raphanus sativus L.) (Iwata et al, 2000, 2004), rice ( Oryza sativa L.) (Mohanty and Khush, 1985; Xu and Shen, 1991; Pooni et al, 1993; Chaubey et al, 1994; Kuo et al, 1997; Taguchi‐Shiobara et al, 1997; Nemoto et al, 2004), soybean [ Glycine max (L.) Merr.] (Spehar, 1995; Spehar and Galwey, 1996; Tukamuhabwa et al, 2002), sugarbeet ( Beta vulgaris L.) (Jolliffe and Arthur, 1993), tobacco ( Nicotiana rustica L.) (Jinks, 1954; Pooni et al, 1997), triticale (× Triticosecale Wittmack) (Mather and Poysa, 1983; Carrillo et al, 1985), and wheat ( Triticum aestivum L.) (Crumpacker and Allard, 1962; Klaimi and Qualset, 1973; Law et al, 1978; Danon and Eyal, 1990; Ghannadha et al, 1995; Wagoire et al, 1998), among others.…”
mentioning
confidence: 99%